Response: Physical Education Learning Assignment Amid the Covid-19 Pandemic - Candra, Oki; Wahyudi, Wahyudi; Prasetyo, Tri (INSPIREE: Indonesian Sport Innovation Review, 2022)
The  purpose  of  the study. The purpose of this study was to find out how deep the response of students to the assignment assigned by the health physical education teacher in determining the number of respondents when the teacher gave physical education assignments. Materials and methods. This research was descriptive quantitative research. The research began by collecting assignments that have been given through online methods to students in the form of google form. The study population was 108 students of SMP IT Raudhatur Rahmah Pekanbaru, Riau. The sample in this study was all students of SMP IT Raudhtaur Rahmah. The sampling technique applied was total sampling. Results. The results obtained based on several assignments that have been given via google form in this study were as follows: For the subject of the passing and catching, dribbling, and shooting on basketball learning, the average scores were 54.25%, 46, 01%, and 42.02%, respectively. Teachers must be more active and creative in packaging the learning process so that it attracts students to take part in the Physical Education learning provided and considering that the response of students in learning physical education during the Covid-19 pandemic was low Conclusions. Online learning was very ineffective as a learning process as it was caused by many factors and can be proven by the low of student response in doing the task which has been given. a solution is needed so that the teaching and learning process can be carried out with an appropriate method so that students are not disadvantaged in the learning activities themselves, which not only receive the knowledge they need, but also includes learning related to the character and emotion that should be given by the teacher in the learning process.